EFFECT OF ALPHA LIPOIC ACID ON MDA LEVELS AND HISTOLOGY OF BRAIN IN TYPE 1 DM - Mahfud, Rania Arif; Lyrawati, Diana; Sarwono, Imam (Malang Neurology Journal, 2017)
Background. Diabetic neuropaty is a condition that can affect pyramidal cells and neuronal cells in theÂ hippocampus. Alpha lipoic acid is effective in pathological conditions where ROS (Reactive Oxygen Species)Â have been implicated, include in brain.Objective. To investigate effects of ALA on oxidative stress in diabetic brain of male Wistar rats.Methods. True experimental design and Posttest Only Control Group are used in this study. Thirty male rats were randomly divided into 5 groups: normal rats without ALA (NTA), diabetic rats without ALA (DTA), diabetic rats with ALA 80 mg, ALA dose 200 mg, and ALA dose 500 mg/kg/day. ALA therapy in mice conducted orally once a day. Diabetes was induced in rats by single intraperitonial injection of streptozotocin (STZ) at 60 mg/kg body weight. The content of malondialdehyde (MDA) in the brain was measured by spectrophotometeric assays. Brain structure (pyramidal cell in hippocampus) was assessed by staining with hematoxylin and eosin.Results. MDA levels in the DTA, DA80 and DA200 is greater than the levels of MDA in the NTA group, but not statistically significant at the MDA values (p = 0,260). Test-Product Moment Pearson correlation showed a weak positive relationship and not significant (r = 0,327) between the groups of NTA, DA80 and DA200 with MDA. No differences pyramidal cell structure between NTA and DTA.Conclusion. The treatment for 4 weeks with ALA had not reduced oxidative stress in diabetic brain.